(untitled) - Binchy, Maeve (Đồng Nai, 2009)
A young country girl comes to live and work in Dublin. Jo is determined to be modern and independent, and to have a wonderful time. But life in a big city is full of strange surprises for a shy country girl ...Gerry Moore is a man with a problem - alcohol. He knows he must give it up, and his family and friends watch nervously as he battles against it. But drink is a hard enemy to fight ...These stories by the Irish writer Maeve Binchy are full of affectionate humour and wit, and sometimes a little sadness.
Keywords: English language,Short stories,Ngôn ngữ tiếng Anh,Truyện ngắn; Readers,Người thích đọc sách